Conservabilidade de noz macadâmi a ( Macadamia integrifolia Maiden & Betche) tratada com gás ozônio - Aires, Eliane Aparecida (2024)
The macadamia nut (Macadamia integrifolia Maiden & Betche), native to Australia, has been attracting the attention of researchers in the food industry due to its growing popularity in both the Brazilian and international markets. Known as the "Queen of Nuts," macadamia is harvested annually, with each tree producing between 30 kg and 40 kg of nuts. During harvesting, the ripe fruits naturally fall from the trees, but in the process, they can become contaminated by fungi (e.g., Aspergillus spp., Fusarium spp., Rhizopus spp.) and bacteria (e.g., Salmonella spp., Escherichia coli, Listeria monocytogenes, Pseudomonas spp., Clostridium spp., Bacillus spp.) upon contact with the soil. To disinfect the nuts, industries use two main methods: chemical treatment with a chlorinated solution and heat treatment, where the nuts are dried at temperatures between 40 °C and 60 °C for up to 30 days. The use of a chlorinated solution increases the moisture content of the nuts, prolonging the drying time, highlighting the need for more effective alternatives to reduce microbial loads. This study evaluated the efficiency of gaseous ozone in treating the nuts after drying, with the shell intact, to eliminate or reduce pathogenic microorganisms that survive the drying process, without altering the physico-chemical characteristics of the nuts. For the experiment, 40 kg of shelled macadamia nuts and 40 kg of control samples (not treated with ozone) were used. The 40 kg of nuts were divided into 8 samples of 5 kg each and treated with gaseous ozone at a concentration of 10 mg/L for 45 minutes. After treatment, the samples were processed, vacuum-packed with nitrogen gas, and stored at 10°C for 180 days and 360 days. The samples were analyzed at three stages: immediately after ozone treatment, after 180 days, and after 360 days of storage. Ozone treatment proved effective in reducing total coliforms, aerobic mesophiles (viable at 30°C), molds, and yeasts. Microbial growth was observed in both the untreated and treated samples, but the levels were significantly lower in the treated samples. The peroxide index results were favorable, with values below the limit of quantification in the ozone-treated samples throughout all storage periods. Although there was a slight increase in moisture and acidity in the treated samples, these increases were not significant. It is concluded that ozone is a promising option for treating macadamia nuts, offering multiple benefits throughout the processing chain.